Server Hardening: Securing Unix-like workstations - Bhardwaj, Yogender (International Journal of Computer Sciences and Engineering, 2015)
In this fast-paced and dynamic world of data communication, systems and software development, and uncontrolled network traffic, security is becoming more and more of an issue. Surprisingly, many organizations, as well as individual users regard security as more of an afterthought (proper security implementation is often enacted after an unauthorized intrusion has already occurred) , a process that is overlooked in favor of increased productivity, convenience, ease of use, and budgetary concerns. Security on Linux systems never stays static. Once secured, the system does not perpetually stay secure. Indeed, the longer one uses the system, the less secure it becomes. This document provides general practices, procedures, planning and tools for creating a secured computing environment for the data center, workplace, or at home. It is aimed for engineers, IT managers, security and system administrators, who are assumed to possess basic system administration skills for Unix-like systems. It addresses basic security vulnerabilities, local and remote intrusion, exploitation and malicious activity techniques valid for all Linux systems.